CONSISTENCY IN PREPAID EXPENSES. - Hackett, Robert P. (The Accounting Review, 1935)
It has been frequently contended that there is no such thing as prepaid interest. Cash is designated by amount only and any cash to the specified amount is as proper for business transactions as any other cash of the same amount. This is not true of other tangible assets. Usually Rent Expense would be debited and Cash credited but in this situation a building is being borrowed and its use is being paid for by what is called rent. However, when money is borrowed an entry is made debiting Cash and crediting Notes Payable. The fact that cash is fungible, that any cash the same in amount may be returned at loan maturity and the fact that buildings are not fangible and may be returned only in exactly the same properties, cloud the issue but do not change it. When payment in kind is indicated it refers to the payment for the use of an asset in the same form as the asset used, as the payment for money borrowed with money, or the payment of rent for a building used in the form of another building. If rent has been paid in advance and the prepaid rent account has been debited and if the lease is broken by agreement, the rent may be reduced as easily as the interest may. This is no more consistent than the other arguments.